Outcomes of community-based nutrition support groups in Dioila Health District, Mali - Dolo, Sulemana Seidu; Mpofu, Limkile (Frontiers in Nutrition, 2026)
BackgroundMalnutrition remains a major public health concern in Mali, particularly in rural districts where food insecurity, limited dietary diversity, and inadequate infant and young child feeding (IYCF) practices persist. The Koulikoro Region continues to experience malnutrition levels above the national average. To strengthen community-level prevention and early detection, the Ministry of Health and partners implemented Nutrition Support Groups (NSGs), facilitated by relais communautaires. Despite their scale-up, evidence on NSG functionality and effectiveness in rural settings, including Dioila Health District, remains limited.ObjectiveTo assess caregiver participation in NSGs, examine self-reported changes in feeding practices, and review recovery outcomes for moderate and severe acute malnutrition using routine health facility records.MethodsA cross-sectional study was conducted in Dioila District between August and September 2024. Caregiver knowledge and practices were assessed using a pre-tested questionnaire, while NSG attendance registers and health facility records provided data on participation and recovery. Descriptive statistics summarized variables, and chi-square and t-tests explored associations between NSG participation and caregiver outcomes.ResultsA total of 227 caregivers from 37 villages participated in the study. NSG attendance was high (91%), and satisfaction with activities reached 78%. Frequent attendees demonstrated significantly higher nutrition knowledge scores (mean = 75.4 vs. 65.0; t = 5.23, p = 0.0002) and better feeding practices (χ2 = 15.67, p = 0.0001) compared with infrequent participants. Self-reported behavior changes included improved complementary feeding (42%), increased dietary diversity (28%), and enhanced hygiene practices (17%). Health facility records indicated strong recovery outcomes, with 99.86% for moderate acute malnutrition (MAM) and 97.86% for severe acute malnutrition (SAM). Reported challenges included limited funding, volunteer fatigue, and occasional community resistance.ConclusionNSGs in Dioila Health District are effective community-based platforms for improving caregiver knowledge, promoting positive feeding practices, and supporting early detection of malnutrition. While facility-based recovery outcomes are strong, sustainability challenges remain. Strengthening supervision mechanisms, ensuring consistent support for community volunteers, and improving referral linkages with health facilities are critical to enhance the effectiveness and long-term sustainability of NSGs in rural Mali.